Factors associated with trajectories of psychological distress for fathers across the early parenting period: A national Australian study - Cooklin, A R; Giallo, Rebecca; Nicholson, Jan; Christensen, Daniel; D'Esposito, Fabrizio (My University, 2014)
Purpose Little is known about the course of fathers’ psychological distress and associated risk factors beyond the postnatal period. Therefore, the current study aimed to: (a) assess the course of distress over 7 years postnatally; (b) identify classes of fathers defined by their symptom trajectories; and (c) identify early postnatal factors associated with persistent symptoms. Method Data from 2,470 fathers in the Longitudinal Study of Australian Children were analysed using latent growth modelling. Fathers’ psychological distress was assessed using the Kessler-6 (Kessler et al. in Arch Psychiatry 60:184–189, 2003) when their children were aged 0–1, 2–3, 4–5 and 6–7 years. Results Overall, distress was highest in the first postnatal year and then decreased over time. Two distinct trajectories were identified. The majority of fathers (92 %) were identified as having minimal distress in the first postnatal year which decreased over time, whilst 8 % had moderate distress which increased over time. Low parental self-efficacy, poor relationship and job quality were associated with ‘persistent and increasing distress’. Conclusions Early postnatal factors associated with fathers’ persistent distress were identified, providing opportunities for early identification and targeted early intervention.
Social Psychiatry and Psychiatric Epidemiology
Keywords: Health -- Mental; Families -- Fathers; Families and relationships; Health and wellbeing; Health; Families; Fathers; Mental; Health and wellbeing; Families and relationships